Ilusi Kota Berkelanjutan di Tengah Problematika Pengelolaan Sampah Perkotaan - Nur Sabrina Kumalasari; Irmayanti Septiana Putri; Fathurrohman Nur Hidayat; Rendy Aprilio Sulaiman; Muhammad Adymas Hikal Fikri (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Rapid urban growth is often linked to the narrative of sustainable development, yet the reality is that fundamental issues remain in the management of urban waste. This paper aims to examine the gap between the concept of a sustainable city and sub-optimal waste management practices. Through a normative legal approach involving an analysis of legislation and relevant literature, it has been found that the implementation of waste management policies continues to face various challenges, such as weak law enforcement, a lack of policy integration, and low levels of public participation. On the other hand, the use of the label ‘sustainable city’ tends to be symbolic and does not yet reflect comprehensive practices. This paper positions the issue of waste as a key indicator in assessing urban sustainability. The novelty of this study lies in its critical approach, which links the discourse on sustainability with the contextual realities of waste management, thereby offering a more reflective and distinct perspective from previous studies.